Effect of serine proteinase from Staphylococcus aureus on in vitro stimulation of human lymphocytes - Prokesová, L; Porwit-Bóbr, Z; Baran, K; Potempa, J; John, C (Immunology letters, 1988)
In a broad concentration range (0.1-100 micrograms/ml) the serine proteinase (SP) from Staphylococcus aureus has no cytotoxic effect on human peripheral blood lymphocytes and does not stimulate them in culture. However, it affects the action of a number of polyclonal activators. In a concentration of 100 micrograms/ml SP completely eliminates blastic transformation after stimulation with B cell mitogens (NDCM, S. aureus and Escherichia coli), lowers the blastic transformation after stimulation with PWM and SPA, and does not affect the blastic transformation after stimulation with PHA. SP (100 micrograms/ml) reduces the concentration of Ig in stimulated cultures (stimulation with PWM, NDCM, S. aureus and E. coli) far below the Ig level of unstimulated controls. This effect can be ascribed to an influence on cell stimulation, not to the proteolytic cleavage of secreted Ig, although SP can partially digest Ig. The effect on lymphocyte stimulation takes place when the SP is added to the culture together with the mitogen, or 18 h after the mitogen. This implies that SP does not affect the first stage of stimulation.
Keywords: Immunoglobulins; In Vitro Techniques; dospělí; Lymphocytes; Staphylococcus aureus; Lymphocyte Activation; aktivace lymfocytů; techniky in vitro; lidé; mitogeny; serinové endopeptidasy; imunoglobuliny; lymfocyty; Mitogens; Serine Endopeptidases; Adult; Humans